Monatomic composite material confinement carbonization precise regulation and control high-capacity fast-charging hard carbon and preparation method and application thereof

By using microporous porous porous carbon carriers, metal compounds and polymer composites in sodium ion batteries, and carbonization in the mesoporum of porous carbon, single atomic metal nanoparticles are introduced, the rate performance and low energy density problems of hard carbon materials in sodium ion batteries are solved, and high capacity fast charging and excellent cycle stability are achieved.

CN119627071APending Publication Date: 2025-03-14ZHUHAI NAYI NEW ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411747978.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The rate performance and low energy density of existing hard carbon materials in sodium ion batteries hinder their commercial application and make it difficult to achieve precise control of complex structures.

Method used

Microporous porous carbon is used as a carrier to combine metal compounds and polymers, and single-atom metal nanoparticles are introduced through one-step carbon thermal reduction, and the domain carbonization is limited to the mesoporum of porous carbon to form an orderly carbon structure to improve sodium storage capacity and fast charging performance.

Benefits of technology

It realizes precise regulation of the material structure, improves sodium storage capacity and fast charging performance, significantly improves the ratio and cycle stability of the material, making it a potential ideal material for high-capacity fast charging hard char in sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005164248680000121
    Figure BDA0005164248680000121
Patent Text Reader

Abstract

The invention discloses high-capacity fast-charging hard carbon with precise regulation and control of confinement carbonization of a monatomic composite material as well as a preparation method and application of the high-capacity fast-charging hard carbon. According to the method, micropore-rich porous carbon is used as a carrier, a metal compound and a high-molecular polymer are compounded for one-step carbon thermal reduction, monatomic metal nanoparticles are introduced into high-capacity fast-charge hard carbon, and the sodium storage capacity of the material is further improved. The micropore-rich porous carbon is coordinated with a metal compound group through a carbon-oxygen single bond and a carbon-carbon single bond, superfine metal nanoparticles are subjected to in-situ carbon thermal reduction in micropores, the metal nanoparticles have high sodium storage capacity, and the micropore structure of the porous carbon can be used as a framework material to solve the problem of poor cycle performance caused by volume expansion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of energy storage, and specifically relates to single-atom composite material confined carbonization precise control high-capacity fast-charging hard carbon and its preparation method and application. Background Art

[0002] The reusability of secondary batteries is in line with the current concept of vigorously developing a sustainable circular economy, which is a prominent advantage of secondary batteries over primary batteries. As a potential large-scale energy storage device, sodium-ion batteries have abundant sodium resources, high cost-effectiveness, and similar chemical properties to lithium-ion batteries. Therefore, they are considered to be the most promising alternative and supplementary energy storage technology to lithium-ion batteries and the future development direction of secondary batteries.

[0003] Hard carbon anode materials are considered to be one of the most promising anode materials for sodium ion batteries due to their abundant resources, diverse structures, high stability and electrochemical performance, low cost, and environmental friendliness. However, the rate performance and low energy density of hard carbon hinder the further commercialization of hard carbon. The size, composition, stacking form, pore distribution, etc. of the carbon layer are very complex. The complex structure and composition are difficult to achieve precise control during the preparation process, making it difficult to accurately customize the properties of the material. In this context, it is of great significance to develop a precisely regulated high-capacity and fast-charging hard carbon material. Summary of the invention

[0004] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing single-atom composite material confined carbonization with precise control and high capacity and fast charging hard carbon.

[0005] The present invention uses micropore-rich porous carbon as a carrier, compounding metal compounds and high molecular polymers for one-step carbon thermal reduction, introducing single-atom metal nanoparticles into high-capacity fast-charging hard carbon, and further improving the sodium storage capacity of the material. The micropore-rich porous carbon coordinates with metal compound groups through carbon-oxygen single bonds and carbon-carbon single bonds, and in-situ carbon thermal reduction of ultrafine metal nanoparticles is carried out in the micropores. The metal nanoparticles have a high sodium storage capacity, and the microporous structure of the porous carbon can be used as a skeleton material to solve the problem of poor cycle performance caused by volume expansion. The mesopores of micropore-rich porous carbon can provide confined space for polymer carbonization, filling, and coating; the polymer material melts, decomposes, carbonizes, and rearranges in the mesopores to gradually form an ordered carbon structure; the orderly stacking of carbon layers forms a sodium ion transmission channel with a width of 0.38-0.40nm, and the wider interlayer spacing can provide sodium ions for rapid intercalation, insertion, and removal, thereby improving the slope capacity and excellent fast-charging performance of the material. The micropores of porous carbon are covered by the ordered carbon layer formed subsequently, and closed pores are formed on the upper layer of the micropores, providing internal space for the filling of sodium ions, further improving the platform capacity of the material. The introduction of metal single atoms occurs in the micropores of porous carbon, and confined carbonization occurs in the mesopores of porous carbon, realizing the optimization and regulation of the material structure at the molecular level. Metal nanoparticles not only improve the sodium storage capacity of the material, but their surface plasmon resonance effect can optimize the electron density distribution and promote charge transfer to improve the conductivity and ion transfer rate of the final product; in addition, the confined carbonization strategy realizes the microstructural reconstruction of hard carbon, which is characterized by anchoring polymers in the mesopores of porous carbon, thereby generating an ordered carbon structure at high temperature. The accumulation of ordered carbon on the micropores of porous carbon realizes the transition from open pores to closed pores; thus achieving the goal of changing from a surface-controlled process to a diffusion-controlled process; the strong charge transfer kinetics, fast ion diffusion characteristics and excellent cycle stability make it a potential ideal candidate for sodium electric hard carbon.

[0006] Another object of the present invention is to provide a single-atom composite material obtained by the above-mentioned preparation method, which is confined carbonization, precisely controlled, and has a high capacity and fast charging hard carbon material.

[0007] Another object of the present invention is to provide the application of the above-mentioned single-atom composite material confined carbonization precise control high-capacity fast-charging hard carbon material in sodium ion batteries.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] A method for preparing a single-atom composite material with confined carbonization, precise control, high-capacity and fast-charging hard carbon material, comprising the following steps:

[0010] (1) fully dissolving the microporous carbon carrier in water, then adding the metal compound and the high molecular polymer, and stirring thoroughly to obtain a completely dispersed aqueous solution;

[0011] (2) freeze-drying the aqueous solution obtained in step (1) to obtain a high-capacity fast-charging hard carbon precursor, and calcining it at 1200-1500° C. for 2-5 hours under an inert gas atmosphere to obtain a single-atom composite high-capacity fast-charging hard carbon crude product;

[0012] (3) The crude single-atom composite high-capacity fast-charging hard carbon obtained in step (2) is crushed, acid-washed, water-washed, dried, and sieved to obtain a single-atom composite high-capacity fast-charging hard carbon material.

[0013] Preferably, the micropore-rich porous carbon carrier in step (1) has a micropore ratio of 85-95%, an average pore diameter of ≤2 nm, and a micropore specific surface area of ​​1200-2500 m 2 / g; More preferably, the micropore ratio of the micropore-rich porous carbon carrier is 90-95%, the average pore diameter is 1.85nm, and the micropore specific surface area is 1800-2500m 2 / g.

[0014] Preferably, the high molecular polymer in step (1) is at least one of polyethylene glycol, polyethylene, polypropylene, polyvinyl chloride and polystyrene; the molecular weight of the high molecular polymer is 1000-5000 g / mol; more preferably, the high molecular polymer is at least one of polyethylene glycol and polystyrene.

[0015] Preferably, the metal compound in step (1) is at least one of silver nitrate, copper nitrate, nickel nitrate and gold hydroxide; more preferably, the metal compound is at least one of silver nitrate and copper nitrate.

[0016] Preferably, in step (1), the micropore-rich porous carbon carrier is fully dissolved in water by stirring at a rotation speed of 750-1000 rpm for 30-60 min.

[0017] Preferably, the sufficient stirring condition in step (1) is stirring at 60-80° C. for 6-10 hours.

[0018] Preferably, the mass ratio of the micropore-rich porous carbon carrier to water in step (1) is (10-30):100; more preferably 10:100.

[0019] Preferably, the concentration of the metal compound in water in step (1) is 5-20 mmol / L; more preferably 5-15 mmol / L.

[0020] Preferably, the mass ratio of the micropore-rich porous carbon support and the high molecular polymer in step (1) is (0.5-2.5):(0-10), wherein the mass of the high molecular polymer is not 0, and more preferably is 1:(0.2-1); the molar ratio of the mass of the micropore-rich porous carbon support to the metal compound is (10-30) g:(0.5-2) mmol; more preferably is 10 g:(0.5-1.5) mmol.

[0021] Preferably, the heating rate of the calcination in step (2) is 3-5°C / min; more preferably 3°C / min.

[0022] Preferably, the calcination temperature in step (2) is 1250-1350° C. and the calcination time is 2-5 h.

[0023] Preferably, the inert gas in step (2) is at least one of nitrogen and argon.

[0024] Preferably, the crushing in step (3) refers to crushing to a particle size Dv50 of 6-9 μm, more preferably 7 μm; the pickling refers to pickling with a mass concentration of 5-10% to an ash content of <0.5%; the water washing refers to water washing to a pH value of 8-9; and the drying refers to drying at 60-100°C for 9-12 hours.

[0025] A single-atom composite material with confined carbonization, precise control, high capacity and fast charging hard carbon material is prepared by the above preparation method.

[0026] The above-mentioned single-atom composite material confined carbonization precisely controls the application of high-capacity and fast-charging hard carbon in sodium-ion batteries.

[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0028] (1) The present invention uses micropore-rich porous carbon as a carrier, and compound metal compounds and high molecular polymers for one-step carbon thermal reduction, and in-situ carbon thermal reduction of ultrafine metal nanoparticles in the micropores to improve the sodium storage capacity of the material; the mesopores of the micropore-rich porous carbon can provide a confined space for polymer carbonization, filling, and coating; the orderly stacking of carbon layers forms a wider sodium ion transmission channel, and the micropores of the porous carbon are covered by the subsequently formed ordered carbon layer, forming closed pores in the upper layer of the micropores, providing internal space for the filling of sodium ions.

[0029] (2) The micropore-rich porous carbon is coordinated with the metal compound groups through carbon-oxygen single bonds and carbon-carbon single bonds, and ultrafine metal nanoparticles are in situ carbon thermally reduced in the micropores. The metal nanoparticles have a high sodium storage capacity, and the microporous structure of the porous carbon can be used as a skeleton material to solve the problem of poor cycling performance caused by volume expansion.

[0030] (3) The mesopores of microporous carbon can provide confined space for polymer carbonization, filling and coating; the polymer material melts, decomposes, carbonizes and rearranges in the mesopores, gradually forming an ordered carbon structure; the orderly stacking of carbon layers forms a sodium ion transmission channel with a width of 0.38-0.40nm, and the wider interlayer spacing can allow sodium ions to be quickly inserted, embedded and removed, thereby improving the slope capacity of the material and excellent fast charging performance.

[0031] (4) The micropores of the porous carbon are covered by the formed ordered carbon layer, and closed pores are formed on the upper layer of the micropores, which provide internal space for the filling of sodium ions, increase the number of closed pores, improve the platform capacity of the material, and make the material have a higher energy density.

[0032] (5) The introduction of metal single atoms occurs in the micropores of porous carbon, and confined carbonization occurs in the mesopores of porous carbon, achieving optimization and regulation of the material structure at the molecular level. Metal nanoparticles not only increase the sodium storage capacity of the material, but their surface plasmon resonance effect can optimize the electron density distribution and promote charge transfer to improve the conductivity and ion transfer rate of the final product; in addition, the confined carbonization strategy realizes the microstructural reconstruction of hard carbon, which is characterized by anchoring polymers in the mesopores of porous carbon, thereby generating an ordered carbon structure at high temperature. The accumulation of ordered carbon on the micropores of porous carbon realizes the transition from open pores to closed pores; and then achieves the goal of changing from a surface-controlled process to a diffusion-controlled process, so that the prepared hard carbon negative electrode has a high sodium storage capacity and excellent rate / cycle performance, making it a potential ideal material for hard carbon. The product obtained by the present invention has an excellent capacity of 378.6mAh / g (platform capacity is 238.5mAh / g), a first efficiency of 91.3%, and excellent rate and cycle performance. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0034] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.

[0035] Example 1

[0036] The method for preparing a single-atom composite material confined carbonization precise control high-capacity fast-charging hard carbon according to the present invention comprises the following steps:

[0037] (1) The micropore ratio of 200g is 90% and the micropore specific surface area is 1800m 2 / g, and the average pore size of 1.85nm was dissolved in 2L of water and stirred at 900rpm for 45min;

[0038] (2) adding a certain amount of silver nitrate and polyethylene glycol (molecular weight 3000 g / mol), stirring at 70° C. for 8 h to form an aqueous solution; the concentration of the silver nitrate in water is 15 mmol / L, and the mass ratio of the porous carbon to the polyethylene glycol is 1:0.2;

[0039] (3) freeze-drying the aqueous solution obtained above to obtain a high-capacity fast-charging hard carbon precursor, and calcining it at 1250° C. for 3 h at a heating rate of 3° C. / min under a nitrogen atmosphere to obtain a single-atom composite high-capacity fast-charging hard carbon crude product;

[0040] (4) The above-mentioned single-atom composite high-capacity fast-charging hard carbon crude material was crushed to a particle size Dv50 of 7 μm and a mass concentration of 5%, and then pickled to an ash content of 0.2%. After pickling, it was washed with water to a pH value of 8, dried at 90°C for 10 hours, and then sieved to obtain a finished product.

[0041] Example 2

[0042] The method for preparing a single-atom composite material confined carbonization precise control high-capacity fast-charging hard carbon according to the present invention comprises the following steps:

[0043] (1) The micropore ratio of 200g is 90% and the micropore specific surface area is 1800m 2 / g, and the average pore size of 1.85nm was dissolved in 2L of water and stirred at 900rpm for 45min;

[0044] (2) adding a certain amount of copper nitrate and polyethylene glycol (molecular weight 3000 g / mol), stirring at 70° C. for 8 h to form an aqueous solution; the concentration of the copper nitrate in water is 15 mmol / L, and the mass ratio of the porous carbon to the polyethylene glycol is 1:0.2;

[0045] (3) freeze-drying the aqueous solution obtained above to obtain a high-capacity fast-charging hard carbon precursor, and calcining it at 1250° C. for 3 h at a heating rate of 3° C. / min under a nitrogen atmosphere to obtain a single-atom composite high-capacity fast-charging hard carbon crude product;

[0046] (4) The above-mentioned single-atom composite high-capacity fast-charging hard carbon crude material was crushed to a particle size Dv50 of 7 μm and a mass concentration of 5%, and then pickled to an ash content of 0.2%. After pickling, it was washed with water to a pH value of 8, dried at 90°C for 10 hours, and then sieved to obtain a finished product.

[0047] Example 3

[0048] The method for preparing a single-atom composite material confined carbonization precise control high-capacity fast-charging hard carbon according to the present invention comprises the following steps:

[0049] (1) The micropore ratio of 200g is 90% and the micropore specific surface area is 1800m 2 / g, and the average pore size of 1.85nm was dissolved in 2L of water and stirred at 900rpm for 45min;

[0050] (2) adding a certain amount of silver nitrate and polystyrene (molecular weight 3000 g / mol), stirring at 70° C. for 8 h to form an aqueous solution; the concentration of the silver nitrate in water is 15 mmol / L, and the mass ratio of the porous carbon to the polystyrene is 1:0.2;

[0051] (3) freeze-drying the aqueous solution obtained above to obtain a high-capacity fast-charging hard carbon precursor, and calcining it at 1250° C. for 3 h at a heating rate of 3° C. / min under a nitrogen atmosphere to obtain a single-atom composite high-capacity fast-charging hard carbon crude product;

[0052] (4) The above-mentioned single-atom composite high-capacity fast-charging hard carbon crude material was crushed to a particle size Dv50 of 7 μm and a mass concentration of 5%, and then pickled to an ash content of 0.2%. After pickling, it was washed with water to a pH value of 8, dried at 90°C for 10 hours, and then sieved to obtain a finished product.

[0053] Example 4

[0054] The method for preparing a single-atom composite material confined carbonization precise control high-capacity fast-charging hard carbon according to the present invention comprises the following steps:

[0055] (1) The micropore ratio of 200g is 95% and the micropore specific surface area is 1800m 2 / g, and the average pore size of 1.85nm was dissolved in 2L of water and stirred at 900rpm for 45min;

[0056] (2) adding a certain amount of silver nitrate and polyethylene glycol (molecular weight 3000 g / mol), stirring at 70° C. for 8 h to form an aqueous solution; the concentration of the silver nitrate in water is 15 mmol / L, and the mass ratio of the porous carbon to the polyethylene glycol is 1:0.2;

[0057] (3) freeze-drying the aqueous solution obtained above to obtain a high-capacity fast-charging hard carbon precursor, and calcining it at 1250° C. for 3 h at a heating rate of 3° C. / min under a nitrogen atmosphere to obtain a single-atom composite high-capacity fast-charging hard carbon crude product;

[0058] (4) The above-mentioned single-atom composite high-capacity fast-charging hard carbon crude material was crushed to a particle size Dv50 of 7 μm and a mass concentration of 5%, and then pickled to an ash content of 0.2%. After pickling, it was washed with water to a pH value of 8, dried at 90°C for 10 hours, and then sieved to obtain a finished product.

[0059] Example 5

[0060] The method for preparing a single-atom composite material confined carbonization precise control high-capacity fast-charging hard carbon according to the present invention comprises the following steps:

[0061] (1) The micropore ratio of 200g is 90% and the micropore specific surface area is 1800m 2 / g, and the average pore size of 1.85nm was dissolved in 2L of water and stirred at 900rpm for 45min;

[0062] (2) adding a certain amount of silver nitrate and polyethylene glycol (molecular weight 3000 g / mol), stirring at 70° C. for 8 h to form an aqueous solution; the concentration of the silver nitrate in water is 5 mmol / L, and the mass ratio of the porous carbon to the polyethylene glycol is 1:0.2;

[0063] (3) freeze-drying the aqueous solution obtained above to obtain a high-capacity fast-charging hard carbon precursor, and calcining it at 1250° C. for 3 h at a heating rate of 3° C. / min under a nitrogen atmosphere to obtain a single-atom composite high-capacity fast-charging hard carbon crude product;

[0064] (4) The above-mentioned single-atom composite high-capacity fast-charging hard carbon crude material was crushed to a particle size Dv50 of 7 μm and a mass concentration of 5%, and then pickled to an ash content of 0.2%. After pickling, it was washed with water to a pH value of 8, dried at 90°C for 10 hours, and then sieved to obtain a finished product.

[0065] Example 6

[0066] The method for preparing a single-atom composite material confined carbonization precise control high-capacity fast-charging hard carbon according to the present invention comprises the following steps:

[0067] (1) The micropore ratio of 200g is 90% and the micropore specific surface area is 1800m 2 / g, and the average pore size of 1.85nm was dissolved in 2L of water and stirred at 900rpm for 45min;

[0068] (2) adding a certain amount of silver nitrate and polyethylene glycol (molecular weight 3000 g / mol), stirring at 70° C. for 8 h to form an aqueous solution; the concentration of the silver nitrate in water is 20 mmol / L, and the mass ratio of the porous carbon to the polyethylene glycol is 1:0.2;

[0069] (3) freeze-drying the aqueous solution obtained above to obtain a high-capacity fast-charging hard carbon precursor, and calcining it at 1250° C. for 3 h at a heating rate of 3° C. / min under a nitrogen atmosphere to obtain a single-atom composite high-capacity fast-charging hard carbon crude product;

[0070] (4) The above-mentioned single-atom composite high-capacity fast-charging hard carbon crude material was crushed to a particle size Dv50 of 7 μm and a mass concentration of 5%, and then pickled to an ash content of 0.2%. After pickling, it was washed with water to a pH value of 8, dried at 90°C for 10 hours, and then sieved to obtain a finished product.

[0071] Example 7

[0072] The method for preparing a single-atom composite material confined carbonization precise control high-capacity fast-charging hard carbon according to the present invention comprises the following steps:

[0073] (1) The micropore ratio of 200g is 90% and the micropore specific surface area is 1800m 2 / g, and the average pore size of 1.85nm was dissolved in 2L of water and stirred at 900rpm for 45min;

[0074] (2) adding a certain amount of silver nitrate and polyethylene glycol (molecular weight 3000 g / mol), stirring at 70° C. for 8 h to form an aqueous solution; the concentration of the silver nitrate in water is 15 mmol / L, and the mass ratio of the porous carbon to the polyethylene glycol is 1:0.5;

[0075] (3) freeze-drying the aqueous solution obtained above to obtain a high-capacity fast-charging hard carbon precursor, and calcining it at 1250° C. for 3 h at a heating rate of 3° C. / min under a nitrogen atmosphere to obtain a single-atom composite high-capacity fast-charging hard carbon crude product;

[0076] (4) The above-mentioned single-atom composite high-capacity fast-charging hard carbon crude material was crushed to a particle size Dv50 of 7 μm and a mass concentration of 5%, and then pickled to an ash content of 0.2%. After pickling, it was washed with water to a pH value of 8, dried at 90°C for 10 hours, and then sieved to obtain a finished product.

[0077] Example 8

[0078] The method for preparing a single-atom composite material confined carbonization precise control high-capacity fast-charging hard carbon according to the present invention comprises the following steps:

[0079] (1) The micropore ratio of 200g is 90% and the micropore specific surface area is 1800m 2 / g, and the average pore size of 1.85nm was dissolved in 2L of water and stirred at 900rpm for 45min;

[0080] (2) adding a certain amount of silver nitrate and polyethylene glycol (molecular weight 3000 g / mol), stirring at 70° C. for 8 h to form an aqueous solution; the concentration of the silver nitrate in water is 15 mmol / L, and the mass ratio of the porous carbon to the polyethylene glycol is 1:1;

[0081] (3) freeze-drying the aqueous solution obtained above to obtain a high-capacity fast-charging hard carbon precursor, and calcining it at 1250° C. for 3 h at a heating rate of 3° C. / min under a nitrogen atmosphere to obtain a single-atom composite high-capacity fast-charging hard carbon crude product;

[0082] (4) The above-mentioned single-atom composite high-capacity fast-charging hard carbon crude material was crushed to a particle size Dv50 of 7 μm and a mass concentration of 5%, and then pickled to an ash content of 0.2%. After pickling, it was washed with water to a pH value of 8, dried at 90°C for 10 hours, and then sieved to obtain a finished product.

[0083] Example 9

[0084] The method for preparing a single-atom composite material confined carbonization precise control high-capacity fast-charging hard carbon according to the present invention comprises the following steps:

[0085] (1) The micropore ratio of 200g is 90% and the micropore specific surface area is 1800m 2 / g, and the average pore size of 1.85nm was dissolved in 2L of water and stirred at 900rpm for 45min;

[0086] (2) adding a certain amount of silver nitrate and polyethylene glycol (3000), stirring at 70° C. for 8 h to form an aqueous solution; the concentration of the silver nitrate in water is 15 mmol / L, and the mass ratio of the porous carbon to the polyethylene glycol is 1:0.2;

[0087] (3) freeze-drying the aqueous solution obtained above to obtain a high-capacity fast-charging hard carbon precursor, and calcining at 1350° C. for 3 h at a heating rate of 3° C. / min under a nitrogen atmosphere to obtain a single-atom composite high-capacity fast-charging hard carbon crude product;

[0088] (4) The above-mentioned single-atom composite high-capacity fast-charging hard carbon crude material was crushed to a particle size Dv50 of 7 μm and a mass concentration of 5%, and then pickled to an ash content of 0.2%. After pickling, it was washed with water to a pH value of 8, dried at 90°C for 10 hours, and then sieved to obtain a finished product.

[0089] Comparative Example 1 (Compared with Example 1, the porous carbon is mesoporous carbon)

[0090] A method for preparing hard carbon comprises the following steps:

[0091] (1) The micropore ratio of 200g is 10%, and the micropore specific surface area is 95m 2 / g, and the mesoporous carbon with an average pore size of 4.27nm was dissolved in 2L of water and stirred at 900rpm for 45min;

[0092] (2) adding a certain amount of silver nitrate and polyethylene glycol (molecular weight 3000 g / mol), stirring at 70° C. for 8 h to form an aqueous solution; the concentration of the silver nitrate in water is 15 mmol / L, and the mass ratio of the porous carbon to the polyethylene glycol is 1:0.2;

[0093] (3) freeze-drying the aqueous solution obtained above to obtain a hard carbon precursor, and calcining it at 1250° C. for 3 h at a heating rate of 3° C. / min under a nitrogen atmosphere to obtain a crude hard carbon product;

[0094] (4) The above-mentioned hard carbon crude material is crushed to a particle size Dv50 of 7 μm and a mass concentration of 5%, and then pickled to an ash content of 0.2%. After pickling, it is washed with water to a pH value of 8, dried at 90°C for 10 hours, and then sieved to obtain a finished product.

[0095] Comparative Example 2 (Compared with Example 1, without adding metal compound)

[0096] A method for preparing hard carbon comprises the following steps:

[0097] (1) The micropore ratio of 200g is 90% and the micropore specific surface area is 1800m 2 / g, and the average pore size of 1.85nm was dissolved in 2L of water and stirred at 900rpm for 45min;

[0098] (2) adding a certain amount of polyethylene glycol (molecular weight 3000 g / mol) and stirring at 70° C. for 8 h to form an aqueous solution; the mass ratio of the porous carbon to the polyethylene glycol is 1:0.2;

[0099] (3) freeze-drying the aqueous solution obtained above to obtain a hard carbon precursor, and calcining it at 1250° C. for 3 h at a heating rate of 3° C. / min under a nitrogen atmosphere to obtain a crude hard carbon product;

[0100] (4) The above-mentioned hard carbon crude material is crushed to a particle size Dv50 of 7 μm and a mass concentration of 5%, and then pickled to an ash content of 0.2%. After pickling, it is washed with water to a pH value of 8, dried at 90°C for 10 hours, and then sieved to obtain a finished product.

[0101] Comparative Example 3 (Compared with Example 1, without adding polymer)

[0102] A method for preparing hard carbon comprises the following steps:

[0103] (1) The micropore ratio of 200g is 90% and the micropore specific surface area is 1800m 2 / g, and the average pore size of 1.85nm was dissolved in 2L of water and stirred at 900rpm for 45min;

[0104] (2) adding a certain amount of silver nitrate and stirring at 70° C. for 8 h to form an aqueous solution; the concentration of the silver nitrate in the water is 15 mmol / L;

[0105] (3) freeze-drying the aqueous solution obtained above to obtain a high-capacity fast-charging hard carbon precursor, and calcining it at 1250° C. for 3 h at a heating rate of 3° C. / min under a nitrogen atmosphere to obtain a crude hard carbon product;

[0106] (4) The above-mentioned hard carbon crude material is crushed to a particle size Dv50 of 7 μm and a mass concentration of 5%, and then pickled to an ash content of 0.2%. After pickling, it is washed with water to a pH value of 8, dried at 90°C for 10 hours, and then sieved to obtain a finished product.

[0107] Comparative Example 4 (Compared with Example 1, the carbonization temperature is 1000°C)

[0108] A method for preparing hard carbon comprises the following steps:

[0109] (1) The micropore ratio of 200g is 90% and the micropore specific surface area is 1800m 2 / g, and the average pore size of 1.85nm was dissolved in 2L of water and stirred at 900rpm for 45min;

[0110] (2) adding a certain amount of silver nitrate and polyethylene glycol (molecular weight 3000 g / mol), stirring at 70° C. for 8 h to form an aqueous solution; the concentration of the silver nitrate in water is 15 mmol / L, and the mass ratio of the porous carbon to the polyethylene glycol is 1:0.2;

[0111] (3) freeze-drying the aqueous solution obtained above to obtain a hard carbon precursor, and calcining it at 1000° C. for 3 h at a heating rate of 3° C. / min under a nitrogen atmosphere to obtain a crude hard carbon product;

[0112] (4) The above-mentioned hard carbon crude material is crushed to a particle size Dv50 of 7 μm and a mass concentration of 5%, and then pickled to an ash content of 0.2%. After pickling, it is washed with water to a pH value of 8, dried at 90°C for 10 hours, and then sieved to obtain a finished product.

[0113] Effect Example 1

[0114] In order to verify the performance of the single-atom composite material confined carbonization precise control of high-capacity fast-charging hard carbon described in the present invention, the products of each embodiment and comparative example were prepared into slurry according to the mass ratio of high-capacity fast-charging hard carbon material: sodium carboxymethyl cellulose (CMC): conductive carbon black (BP) = 90:5:5 and the negative electrode sheet of the sodium ion battery was prepared. The metal sodium sheet was used as the battery, and the electrolyte was 1 mol / L NaPF 6The button cell was assembled in a ternary mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) dissolved in a volume ratio of 1:1:1. Then, the button half-cell was charged and discharged using the CT2001A blue electric test system with a test voltage range of 0.0-2.0V at a rate of 0.1C. The first discharge capacity and the first coulomb efficiency of the product were recorded, and then the cycle was repeated 100 times to record the capacity retention rate of the discharge capacity. Fast charging performance test: voltage range 0-2V, 5 cycles at current densities of 0.1C, 0.25C, 0.5C, 1.0C, 2.5C, 5.0C, and 10.0C, respectively. 0-0.1V is the platform capacity, and 0.1V-2.0V is the slope capacity. The ratio of the discharge capacity at 5C to the discharge capacity at 1C is recorded, that is, the 5C / 1C capacity retention rate; the results are shown in Table 1.

[0115] Table 1

[0116]

[0117] It can be clearly seen from Table 1 that the single-atom composite material confined carbonization precisely controlled high-capacity fast-charging hard carbon material prepared by the preparation method of the present invention has a first discharge specific capacity of up to 378.6 mAh / g, a first platform discharge specific capacity of 238.5 mAh / g, a first coulombic efficiency of 91.3%, a capacity retention rate of 95.8% after 100 cycles, and a 5C / 1C capacity retention rate of 89.8, with excellent comprehensive performance.

[0118] In the process of preparing high-capacity and fast-charging hard carbon materials, if the porous carbon is not rich in micropore structure, as shown in Comparative Example 1, the discharge specific capacity of the prepared material is low, especially the discharge specific capacity of the platform, and the larger pore size of the mesoporous material leads to a lower first efficiency, aggravated side reactions during the cycle, and poor cycle performance.

[0119] The use of metal compounds is crucial in the preparation process, otherwise, as shown in Comparative Example 2, the sodium storage capacity of the material cannot be improved, and the surface plasmon resonance effect of ultrafine metal nanoparticles can optimize the electron density distribution and promote charge transfer to improve the rate performance of the material.

[0120] The use of high molecular polymers is crucial in the preparation process, otherwise, as shown in Comparative Example 3, the polymer cannot be carbonized, filled, or coated in the mesopores of the porous carbon material to confine its growth; it cannot generate a wider sodium ion channel and it cannot achieve the transition from open pores to closed pores, thus affecting the discharge capacity and rate performance of the material.

[0121] As shown in Comparative Example 4, if the carbonization temperature is low, the carbon layers cannot be stacked by high temperature to form a complete twisted carbon structure, that is, an inner cavity cannot be formed, usually called a closed cell, thereby affecting the discharge platform capacity and the first effect of the material.

[0122] The single-atom composite material confined carbonization precise control high-capacity fast-charging hard carbon material prepared by the present invention has excellent electrochemical properties, including significant cycle stability and fast-charging and high-capacity performance. The main reasons are: (1) The fast-charging performance is attributed to its excellent conductivity and wide interlayer spacing. The surface plasmon resonance effect of metal nanoparticles can optimize the electron density distribution and promote charge transfer to improve the conductivity and ion transfer rate of the final product; the wide interlayer spacing can provide sodium ions for rapid intercalation, insertion and extraction, thereby improving the slope capacity and excellent fast-charging performance of the material; (2) The high-capacity performance is attributed to the high sodium storage capacity of metal nanoparticles. The micropores of porous carbon are covered by the subsequently formed ordered carbon layer, and closed pores are formed on the upper layer of the micropores, which increases the number of closed pores and further improves the sodium storage capacity of the material. (3) The long-cycle performance is attributed to the microporous structure of porous carbon, which can be used as a skeleton material to solve the problem of poor cycle performance caused by volume expansion.

[0123] In summary, the introduction of metal single atoms occurs in the micropores of porous carbon, and confined carbonization occurs in the mesopores of porous carbon, achieving optimization and regulation of the material structure at the molecular level. Metal nanoparticles not only increase the sodium storage capacity of the material, but their surface plasmon resonance effect can optimize the electron density distribution and promote charge transfer to improve the conductivity and ion transfer rate of the final product; in addition, the confined carbonization strategy achieves the microstructural reconstruction of hard carbon, which is characterized by anchoring polymers in the mesopores of porous carbon, thereby generating an ordered carbon structure at high temperature. The accumulation of ordered carbon on the micropores of porous carbon realizes the transition from open pores to closed pores; thus achieving the goal of changing from a surface-controlled process to a diffusion-controlled process, so that the prepared hard carbon anode has a high sodium storage capacity and excellent rate / cycle performance.

[0124] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing single-atom composite material confined carbonization with precise control of high-capacity and fast-charging hard carbon, characterized in that: The following steps are involved: (1) fully dissolving the microporous carbon carrier in water, then adding the metal compound and the high molecular polymer, and stirring thoroughly to obtain a completely dispersed aqueous solution; (2) freeze-drying the aqueous solution obtained in step (1) to obtain a high-capacity fast-charging hard carbon precursor, and calcining under an inert gas atmosphere to obtain a single-atom composite high-capacity fast-charging hard carbon crude product; (3) The crude single-atom composite high-capacity fast-charging hard carbon obtained in step (2) is crushed, acid-washed, water-washed, dried, and sieved to obtain a single-atom composite high-capacity fast-charging hard carbon material.

2. The method for preparing high-capacity and fast-charging hard carbon by precise control of confined carbonization of single-atom composite materials according to claim 1, characterized in that: The micropore-rich porous carbon carrier in step (1) has a micropore ratio of 85-95%, an average pore diameter of ≤2nm, and a micropore specific surface area of ​​1200-2500m 2 / g; The high molecular polymer in step (1) is at least one of polyethylene glycol, polyethylene, polypropylene, polyvinyl chloride and polystyrene; the molecular weight of the high molecular polymer is 1000-5000 g / mol; The metal compound in step (1) is at least one of silver nitrate, copper nitrate, nickel nitrate and gold hydroxide; The mass ratio of the micropore-rich porous carbon support to the high molecular polymer in step (1) is (0.5-2.5):(0-10), wherein the mass of the high molecular polymer is not 0; The molar ratio of the mass of the micropore-rich porous carbon carrier to the metal compound is (10-30) g: (0.5-2) mmol.

3. The method for preparing high-capacity and fast-charging hard carbon by precise control of confined carbonization of single-atom composite materials according to claim 2, characterized in that: The micropore ratio of the micropore-rich porous carbon carrier in step (1) is 90-95%, the average pore diameter is 1.85 nm, and the micropore specific surface area is 1800-2500 m 2 / g; The high molecular weight polymer in step (1) is at least one of polyethylene glycol and polystyrene; The metal compound in step (1) is at least one of silver nitrate and copper nitrate; The mass ratio of the micropore-rich porous carbon carrier to the high molecular polymer in step (1) is 1:(0.2-1); The molar ratio of the mass of the micropore-rich porous carbon carrier to the metal compound is 10 g: (0.5-1.5) mmol.

4. The method for preparing high-capacity and fast-charging hard carbon by precise control of confined carbonization of single-atom composite materials according to claim 1, characterized in that: The calcination temperature in step (2) is 1200-1500° C. and the calcination time is 2-5 hours; The heating rate of the calcination in step (2) is 3-5°C / min.

5. The method for preparing high-capacity and fast-charging hard carbon by precise control of confined carbonization of single-atom composite materials according to claim 4, characterized in that: The calcination temperature in step (2) is 1250-1350° C. and the calcination time is 2-5 hours.

6. The method for preparing high-capacity and fast-charging hard carbon by precise control of confined carbonization of single-atom composite materials according to claim 1, characterized in that: The concentration of the metal compound in water in step (1) is 5-20 mmol / L; The mass ratio of the micropore-rich porous carbon carrier to water in step (1) is (10-30):

100.

7. The method for preparing high-capacity and fast-charging hard carbon by precise control of confined carbonization of single-atom composite materials according to claim 6, characterized in that: The concentration of the metal compound in water in step (1) is 5-15 mmol / L; The mass ratio of the micropore-rich porous carbon carrier to water in step (1) is 10:

100.

8. The method for preparing high-capacity and fast-charging hard carbon by precise control of confined carbonization of single-atom composite materials according to claim 1, characterized in that: The micropore-rich porous carbon support in step (1) is fully dissolved in water by stirring at a speed of 750-1000 rpm for 30-60 min; The sufficient stirring condition in step (1) is stirring at 60-80° C. for 6-10 hours; The inert gas in step (2) is at least one of nitrogen and argon; The crushing in step (3) refers to crushing to a particle size Dv50 of 6-9 μm, more preferably 7 μm; the pickling refers to pickling with a mass concentration of 5-10% to an ash content of <0.5%; the water washing refers to water washing to a pH value of 8-9; and the drying refers to drying at 60-100°C for 9-12 hours.

9. Single-atom composite material with confined carbonization, precise control, high capacity and fast charging hard carbon obtained by the preparation method according to any one of claims 1 to 8.

10. Application of the single-atom composite material described in claim 9 in sodium ion batteries through precise control of confined carbonization and high-capacity, fast-charging hard carbon.

Citation Information

Cited By

  • Method for preparing hard carbon through limited-range thermal conversion of non-carbon-forming polymer into carbon and application of hard carbon in negative electrode of alkali metal ion battery

    CN121470469A